ALGORITMA NAIVE BAYES UNTUK PENENTUAN PKH (PROGRAM KELUARGA HARAPAN) BERBASIS SISTEM PENDUKUNG KEPUTUSAN (STUDI KASUS : KELURAHAN KARANGANYAR GUNUNG SEMARANG) - Amin Abdullah Sidiq; Febrian Wahyu Christanto (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2020)
The Family Hope Program is a program of providing conditional social assistance to poor families that are designated as PKH beneficiary families. As a conditional social assistance program, PKH opens access to poor families especially pregnant women and children to take advantage of the various health service facilities (Faskes) and educational service facilities (Fasdik) available around them. The benefits of PKH also have begun to be encouraged to cover people with disabilities and the elderly by maintaining the level of social welfare in accordance with the mandate of the constitution and the President's Nawacita. In the area of Karanganyar Gunung Village in Semarang, this assistance is given if the prospective recipient is deemed to have met the requirements and criteria for example job status, house status, number of dependents, education component, electricity expenditure, and water. This research was conducted because of the many weaknesses in the scoring system used. In Karanganyar Gunung Village, the assessment is still subjective and manual, this is of course in the distribution of PKH (Family Hope Program) aid recipients is not evenly distributed and mis-targeted. Therefore, this research was conducted to create a decision support system called E-PKH that uses the Naïve Bayes classification algorithm method which produces the labels